Perceptions and Nationalism Attitudes of PGSD Students toward Civic Education Learning in Parepare - Ritha Tuken (Darul Yasin Al Sys, 2026)
Although Civic Education learning has received increasing attention in previous studies, research specifically examining the relationship between students’ perceptions of Civic Education learning and their nationalism attitudes remains limited, particularly among PGSD students in Parepare. This study aims to analyze the relationship between students’ perceptions of Civic Education learning and their nationalism attitudes. A quantitative approach with a survey design was employed, involving 120 respondents selected through proportional random sampling. Data were collected using a structured questionnaire and analyzed using descriptive statistics and Pearson correlation analysis. The findings indicate that students’ perceptions of Civic Education learning were in the good category (M = 3.87), while their nationalism attitudes were categorized as high (M = 4.12). The correlation analysis revealed a significant positive relationship between students’ perceptions and nationalism attitudes (r = 0.68, p < .05). These results suggest that positive perceptions of Civic Education learning are associated with stronger nationalism attitudes among students. This study contributes to the theoretical development of civic education and nationalism studies by expanding understanding of how instructional perceptions relate to students’ civic attitudes in higher education contexts. Practically, the findings imply that educators should adopt innovative, contextual, and value-based teaching strategies to strengthen the effectiveness of Civic Education learning and support the development of nationalism attitudes.